(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Operating room (OR) environments are physically demanding, particularly for the healthcare professionals who spend long hours standing during surgeries. Surgeons, nurses, and technicians often endure discomfort, and over time, this prolonged standing can lead to significant health problems like musculoskeletal disorders (MSDs), back pain, and leg fatigue. Despite the common occurrence of these issues, there is limited support or intervention from employers to address the physical strain. This study explores how prolonged standing impacts the health of operating room staff, the symptoms they experience, the available treatment options, and the role of employer-provided interventions. Methods: After Rehman College of Allied Health Sciences (RCAHS) ethical research committee approval a Descriptive Cross-Sectional Study was conducted. A total of 112 OT staff were included in the study. Data was collected through a questionnaire and analysed using SPSS version 20.0. Objectives: (I) To identify the risk of Prolonged standing during surgical procedures on health and work performance of the OR staff. (II) To assess the knowledge for enhancing working conditions and minimizing health risks associated with Prolonged standing. Results: Many operating rooms staff experience significant discomfort from prolonged standing. About 60.7% spend over 75% of their shift on their feet. Common symptoms include extreme fatigue (48.2%), back pain (43.8%), and leg pain (35.7%). Only 23.4% received interventions like therapy or medication. Most (65.2%) reported no employer support to reduce the prolonged standing effects. Despite this, 56.3% believed addressing prolonged standing would boost job satisfaction and performance. Additionally, 59.8% felt their health concerns were ignored by management. Conclusion: The findings highlight the significant health impacts of prolonged standing on operating room staff, including fatigue and discomfort. Most staff feel unsupported by employers, reflecting a gap in workplace wellness practices. Addressing these concerns could enhance job satisfaction and performance. Simple, effective solutions are essential to alleviate physical strain.